Water Management Challenges in the Context of Agricultural Intensification and Endemic Fluorosis: The Case of Yuanmou County - Fang J; Wu XN; Xu, J.C.; Yang XF; Song XX; Wang GA; Yan MS; Yan M; Wang DN. (Springer, 2011)
Yuanmou County in Yunnan Province, China is situated in a dry hot valley where annual evaporation is almost six times the annual rainfall and thus the county suffers from chronic water shortages. Since the early 1980s the county has taken advantage of local warm climate and focused its economic development strategy on commercial vegetable plantations. This strategy successfully brings high income to the local government and farmers, but increases water consumption and adds an extra stressor to the already diminished water resources. Yuanmou County is one of the endemic fluorosis hotspots in China where both dental and skeletal fluorosis cases have been found among local villagers that were diagnosed as being water-borne. Despite measures to adapt to water shortages and control fluorosis taken by the local government and communities, new challenges are emerging. Herein, we describe the water management challenges facing the county as well as document the coping strategies adopted by the government and communities, analyze remaining and emerging challenges, and suggest an ecohealth framework for better management of water resources in Yuanmou.